2006
DOI: 10.1001/archsurg.141.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Rupture of Hepatocellular Carcinoma

Abstract: To review the management of spontaneous ruptured hepatocellular carcinoma in the acute phase, the definitive treatment after hemostasis, and the prognosis. Data Sources: A MEDLINE search was undertaken to identify articles in English from 1970 to 2004 using the key words "hepatocellular carcinoma," "spontaneous rupture," "therapeutic embolization," and "laparoscopy." Additional articles were identified by a manual search of the references from the key articles.Study Selection: There were no exclusion criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
270
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 211 publications
(291 citation statements)
references
References 62 publications
4
270
7
Order By: Relevance
“…The incidence of HCC rupture is higher in Asia than in Western countries, ranging from 2.3% to 26% in Asia compared with less than 3% in the West 4, 5. The incidence of HCC rupture in our study was 5.3%, lower than in a 1995 study in Taiwan (26%) 13.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…The incidence of HCC rupture is higher in Asia than in Western countries, ranging from 2.3% to 26% in Asia compared with less than 3% in the West 4, 5. The incidence of HCC rupture in our study was 5.3%, lower than in a 1995 study in Taiwan (26%) 13.…”
Section: Discussioncontrasting
confidence: 76%
“…The incidence of HCC rupture in our study was 5.3%, lower than in a 1995 study in Taiwan (26%) 13. Other studies reported that ruptured HCC is associated with high in‐hospital mortality, above 25% 4, 5. In the current study, 23% of the patients with tumor ruptures died during their hospital stays.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations